The Synthesis of Hydroxybutyrate-Based Block Polyurethane from Telechelic Diols with Robust Thermal and Mechanical Properties - Dan Xue; Xiaodong Fan; Zengping Zhang; Wei Lv (Journal of Chemistry)
A series of novel amphiphilic block polyurethanes (PUHE) have been successfully synthesized by solution polymerization of the derived PHB-diol and poly(ethylene glycol) with a coupling agent of 1,6-hexamethylene diisocyanate (HDI), while the PHB-diol was prepared via the transesterification of PHB and ethylene glycol. The hydroxyl contents in PHB-diols range from 1.36 to 1.99 (the molar ratio) as determined by nonaqueous titration. The molecular weight and chemical compositions of PUHE and PHB-diol were investigated by GPC, 1H NMR, and FTIR in detail, which confirm the successful synthesis of PUHE. The tensile strength and elongation at break of PUHE could reach as high as 20 MPa and 210%, as the content of PHB in PUHE is 33%. TGA curves indicate that block-bonding between PHB-diol and PEG increases the thermal stability of PHB-diol. Film degradation of PUHE was studied by weight loss and scanning electron microscope (SEM). It could be concluded that degradation occurred gradually from the surface to the inside and that the degradation rate could be controlled by adjusting the PHB/PEG ratios. These properties make PUHE able to be used as a biodegradable thermoplastic elastomer.